Educational Doomscrolling and Academic Productivity Decline: An Educational Management Perspective in the Era of Digital Information Overload - Risza Presty Rumani (Gestion Educativa, 2026)
The phenomenon of ghost attendance, or pseudo-attendance, in digital learning is a serious and The proliferation of digital media and social platforms has given rise to a phenomenon known as educational doomscrolling, the habitual, compulsive consumption of predominantly negative digital content during academic hours. This systematic literature review investigates the relationship between educational doomscrolling and academic productivity decline within the framework of educational management in the digital information overload era. Drawing on 20 peer-reviewed sources published between 2022 and 2025, this study synthesizes empirical evidence on how continuous exposure to negative digital content disrupts cognitive load, reduces concentration, impairs study time management, and ultimately undermines academic achievement. Findings reveal that students who engage in prolonged doomscrolling exhibit significant decreases in assignment completion rates, GPA performance, and self-regulated learning behaviors. From an educational management perspective, institutional responses remain inadequate, with most universities lacking formal digital wellness policies or structured interventions. This review proposes a Digital Academic Wellness Framework (DAWF) comprising four strategic components: policy formulation, pedagogical adaptation, student digital literacy development, and mental health integration. The implications for educational administrators, faculty, and policymakers are discussed, with recommendations for evidence-based practices to mitigate the adverse effects of information overload on academic productivity